Case reportSAPHO syndrome: case report - Misiak-Gałązka, Magdalena; Jeziorkowska, Renata; Sikorska-Siudek, Katarzyna; Wolska, Hanna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
SAPHO syndrome is characterized by synovitis, acne, pustulosis, hyperostosis and osteitis. Dermatological manifestations include palmoplantar pustulosis, pustular psoriasis in other sites of the body, psoriasis vulgaris, acne (often severe, conglobata or fulminans), hidradenitis suppurativa. The vertebral arthritis associated with the disease belongs to a group of seronegative spondyloarthropathies. The aim was presenting a case of SAPHO syndrome which developed in a patient suffering from palmoplantar pustulosis. We present a patient who developed pustulosis palmoplantaris and low back pain at the same time. The diagnosis of SAPHO syndrome was established on clinical appearance and results of additional tests. The patient was treated with methotrexate in dose initially 15 mg, then 25 mg once a week, non-steroidal anti-inflammatory drugs and topical treatment with improvement. The pain of the chest wall or multifocal arthritis affecting the patient with palmoplantar pustulosis or severe acne should arouse suspicions of SAPHO syndrome.